Newborn screening and the screening laboratory: past, present and future - Anita Boelen; Annemieke C Heijboer (European Thyroid Journal)
Thyroid hormone (TH) is essential for brain development in utero and during the first 2 to 3 years of life. The negative effects of TH deficiency on brain development are irreversible. Early detection of TH deficiency in neonates (congenital hypothyroidism (CH) through newborn screening (NBS)) allows for early treatment, thereby preventing brain damage. Screening for CH began in 1973 with the measurement of total thyroxine (T4) in dried blood spots. The enhanced sensitivity of thyroid-stimulating hormone (TSH) measurement has prompted a shift in the approach to NBS for CH. Currently, worldwide, the majority of NBS programs for CH employ TSH as the primary screening marker. However, a select few programs still utilize T4 as the primary marker, enabling the detection of both primary and central CH. This review provides an overview of the laboratory aspects of the screening on CH from the start of screening to the present.